Evaluation of Axial Flow Impeller Fabrication Process by Wire Arc Additive Manufacturing and Machining - Shinichiro Ejiri (Engineering Proceedings, 2024)
An evaluation was conducted on the fabrication of an axial flow impeller by a hybrid system of wire arc additive manufacturing and machining. First, a four-bladed stainless steel axial flow impeller was fabricated to measure the number of chips and fabrication time. Next, axial flow impellers with different numbers of blades were designed and compared with those fabricated only by machining from a round bar. In both cases, the number of chips was reduced by approximately 80% by using this system. On the other hand, the increase in the number of blades reduced the difference in fabrication time, which was almost the same with six blades. In conclusion, the use of this system is an option from the viewpoint of reducing environmental impact; however, it is not necessarily advantageous in terms of fabrication time.